2016
DOI: 10.1371/journal.pone.0156005
|View full text |Cite|
|
Sign up to set email alerts
|

Arterial Transit Time Mapping Obtained by Pulsed Continuous 3D ASL Imaging with Multiple Post-Label Delay Acquisitions: Comparative Study with PET-CBF in Patients with Chronic Occlusive Cerebrovascular Disease

Abstract: Arterial transit time (ATT) is most crucial for measuring absolute cerebral blood flow (CBF) by arterial spin labeling (ASL), a noninvasive magnetic resonance (MR) perfusion assessment technique, in patients with chronic occlusive cerebrovascular disease. We validated ASL-CBF and ASL-ATT maps calculated by pulsed continuous ASL (pCASL) with multiple post-label delay acquisitions in patients with occlusive cerebrovascular disease. Fifteen patients underwent MR scans, including pCASL, and positron emission tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…A pseudo-continuous ASL (pCASL, GE's product version) prepped 3D spiral fast spin-echo (FSE) acquisition combined with background suppression was used for calculation of MRI perfusion images [18]. Details of the method are described elsewhere [19]. In brief, the labeling duration for ASL preparation was 1.5 s, and the 3D-FSE readout signal was obtained with an interleaved stack of 7-arm acquisitions for each excitation at each of 36-42 centrically ordered slice encodes.…”
Section: Arterial Spin Labeling (Asl) Methods For Cbfmentioning
confidence: 99%
See 1 more Smart Citation
“…A pseudo-continuous ASL (pCASL, GE's product version) prepped 3D spiral fast spin-echo (FSE) acquisition combined with background suppression was used for calculation of MRI perfusion images [18]. Details of the method are described elsewhere [19]. In brief, the labeling duration for ASL preparation was 1.5 s, and the 3D-FSE readout signal was obtained with an interleaved stack of 7-arm acquisitions for each excitation at each of 36-42 centrically ordered slice encodes.…”
Section: Arterial Spin Labeling (Asl) Methods For Cbfmentioning
confidence: 99%
“…In brief, the labeling duration for ASL preparation was 1.5 s, and the 3D-FSE readout signal was obtained with an interleaved stack of 7-arm acquisitions for each excitation at each of 36-42 centrically ordered slice encodes. The labeling slab is automatically set at a level 2 cm inferior to the scan range, and images were acquired with the following parameters: 240 mm FOV; 128 × 128 matrix; in-plane resolution 1.8 mm; slice thickness 4.5 mm; fixed postlabeling delay (PLD) 2.0 s [19]. The number of excitations for the acquisition was three, and the total scan duration was 4 min 10 s. For blood flow quantification, an approximate proton density weighted image was also obtained with the same acquisition parameters.…”
Section: Arterial Spin Labeling (Asl) Methods For Cbfmentioning
confidence: 99%
“…For instance, moderate to high similarity between 3.0T ASL and 15 O positron emission tomography CBF images was reported in vascular and dementia cohorts. 27,33 Wang et al 26 and Qiu et al 34 reported moderate similarity between multi-PLD ASL and CT in patients with delayed blood delivery, ie, long ATT. Liu et al compared 3.0T ASL and SPECT in young healthy adults and reported a high similarity between CBF images.…”
Section: Discussionmentioning
confidence: 99%
“…We examined ENABLE performance against a conventional (CONV) multi‐PLD ASL analysis, ie, no image quality evaluation . We modeled multi‐PLD images with an established ASL kinetic model tool (BASIL) to generate CBF images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation